Methods of boosting creativity of future engineers-pedagogues in the process of professional knowledge acquisition - Volkova, N. V. (Problems of Engineer-Pedagogical Education, 2018)
The article reveals the problems of upgrading the system of vocational training and methodologies of teaching professional disciplines in the process of training engineers-pedagogues in the field of food technologies. The purpose of the article is to disclose optimum and efficient methods of the development of future experts’ creativity. The research into these problems is conducted by the author on the basis of the analysis, generalization and specification of the best pedagogical practices concerning the organization of the teaching and learning process in the system of vocational training of engineers-pedagogues in the sphere of food technologies. The author puts a strong emphasis on the fact that the use of independent work, project methods, case methods, problem-solving methods and creative task methods promotes the development of future teachers’ creativity, their readiness to search, create, consider and apply the latest educational trends, to use techniques aimed at honing their own creative skills. This also enables them to master the system of heuristic methods and techniques and to acquire skills which will be useful while introducing the latest branch technologies of the food industry in the course of vocational education. The results received by the author have direct entry into the practice of training engineerspedagogues in the system of higher education.